Revision of the aphyonid genus Aphyonus (Teleostei, Ophidiiformes) with a new genus and two new species - Nielsen, Jørgen G. (Zootaxa, 2015)
The cosmopolitan, deep sea, aphyonid genus Aphyonus is known from less than 100 specimens. The type species A. gelatinosus Günther, 1878 and three additional valid species, A. brevidorsalis Nielsen, 1969, A. bolini Nielsen, 1974, and A. rassi Nielsen, 1975 were all based on single specimens. Since then several specimens have been caught of which 52 are examined for the present revision. Most of the specimens are referred to A. gelatinosus but also to A. bolini and A. rassi. A result of the enlarged material is that the type species, A. gelatinosus, is found to differ so much from the remaining species that a new genus, Paraphyonus, is established for these species. Furthermore two new species of Paraphyonus are here described, P. iselini based on six specimens from the tropical northwestern Atlantic Ocean and P. merretti based on three specimens from the northeastern Atlantic Ocean. The present knowledge of the variation of the Paraphyonus species makes it relevant to transfer Barathronus solomonensis Nielsen & Møller, 2008 to this genus.